Neutron dark matter decays and correlation coefficients of neutron β−-decays - A.N. Ivanov; R. Höllwieser; N.I. Troitskaya; M. Wellenzohn; Ya.A. Berdnikov (Nuclear Physics B, 2019)
As we have pointed out in (arXiv:1806.10107 [hep-ph]), the existence of neutron dark matter decay modes n→χ+anything, where χ is a dark matter fermion, for the solution of the neutron lifetime problem changes priorities and demands to describe the neutron lifetime τn=888.0(2.0)s, measured in beam experiments and defined by the decay modes n→p+anything, in the Standard Model (SM). The latter requires the axial coupling constant λ to be equal to λ=−1.2690 (arXiv:1806.10107 [hep-ph]). Since such an axial coupling constant is excluded by experimental data reported by the PERKEO II and UCNA Collaborations, the neutron lifetime τn=888.0(2.0)s can be explained only by virtue of interactions beyond the SM, namely, by the Fierz interference term of order b∼−10−2 dependent on scalar and tensor coupling constants. We give a complete analysis of all correlation coefficients of the neutron β−-decays with polarized neutron, taking into account the contributions of scalar and tensor interactions beyond the SM with the Fierz interference term b∼−10−2. We show that the obtained results agree well with contemporary experimental data that does not prevent the neutron with the rate of the decay modes n→p+anything, measured in beam experiments, to have dark matter decay modes n→χ+anything.